CropCircDB: a comprehensive circular RNA resource for crops in response to abiotic stress. (6th May 2019) - Wang, Kai; Wang, Chong; Guo, Baohuan; Song, Kun; Shi, Chuanhong; Jiang, Xin; Wang, Keyi; Tan, Yacong; Wang, Lequn; Wang, Lin; Li, Jiangjiao; Li, Ying; et al.
Abstract: Circular RNA (circRNAs) may mediate mRNA expression as miRNA sponge. Since the community has paid more attention on circRNAs, a lot of circRNA databases have been developed for plant. However, a comprehensive collection of circRNAs in crop response to abiotic stress is still lacking. In this work, we applied a big-data approach to take full advantage of large-scale sequencing data, and developed a rich circRNA resource: CropCircDB for maize and rice, later extending to incorporate more crop species. We also designed a metric: stress detections score, which is specifically for detecting circRNAs under stress condition. In summary, we systematically investigated 244 and 288 RNA-Seq samples for maize and rice, respectively, and found 38 785 circRNAs in maize, and 63 048 circRNAs in rice. This resource not only supports user-friendly JBrowser to visualize genome easily, but also provides elegant view of circRNA structures and dynamic profiles of circRNA expression in all samples. Together, this database will host all predicted and validated crop circRNAs response to abiotic stress.